2014
DOI: 10.1590/0037-8682-0042-2014
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of canine visceral leishmaniasis in Barra Mansa, State of Rio de Janeiro

Abstract: Introduction: In Brazil, visceral leishmaniasis (VL) has spread to various regions. This study reports canine cases of VL in Barra Mansa, where human VL cases were recently reported. Methods: Using the human index case, a canine survey was performed by dual-path platform immunochromatography and enzyme-linked immunosorbent assay. Seropositive animals were euthanized. Cultures were collected to detect Leishmania parasites. Results: Serological tests detected 141 canine VL cases, and Leishmania chagasi were isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…The age of the dogs ranged from 1 to 7 years in 39 (81%) animals, five (11%) were older than 7 years, and four (8%) were less than 11 months old. The dogs were from the town of Barra Mansa (22°32’25.19” S and 44°10’35.33” W), Rio de Janeiro State, Brazil, a ZVL-endemic area with reports of cases in dogs [24] and humans [25]. All animals were privately owned and tested seropositive for anti- Leishmania antibodies by a rapid immunochromatographic test (Dual Path Platform, DPP ® ) and by enzyme immunoassay (ELISA).…”
Section: Methodsmentioning
confidence: 99%
“…The age of the dogs ranged from 1 to 7 years in 39 (81%) animals, five (11%) were older than 7 years, and four (8%) were less than 11 months old. The dogs were from the town of Barra Mansa (22°32’25.19” S and 44°10’35.33” W), Rio de Janeiro State, Brazil, a ZVL-endemic area with reports of cases in dogs [24] and humans [25]. All animals were privately owned and tested seropositive for anti- Leishmania antibodies by a rapid immunochromatographic test (Dual Path Platform, DPP ® ) and by enzyme immunoassay (ELISA).…”
Section: Methodsmentioning
confidence: 99%
“…Seven cases described in this study originated in the Atlantic forest region in the municipality of Rio de Janeiro, on the eastern slope of the Pedra Branca massif, in the lowlands in the Jacarepaguá district, where cases of CVL have been described since the 1980s (11) . On the other hand, in Barra Mansa, a municipality located in the southern region of the State of Rio de Janeiro, CVL was only recently diagnosed (12) and one of the cases described in this study came from this region.…”
Section: Domestic Dogs Are Naturally Infected With Different Species mentioning
confidence: 56%
“…The inferior rates of detection of L. infantum in SK and BM may be due to the lower frequency of active infection in these tissues, a possibly lower parasite load when compared to LN and SP, or the stage of infection, which was not evaluated in this study. Both LN [ 4 , 6 , 14 , 15 ] and SP [ 13 , 16 ] have been recommended as the most suitable tissues for the diagnosis of L. infantum infection in dogs. Obtaining a LN biopsy is generally considered more practical and clinically safe than obtaining a SP biopsy and some professionals avoid SP sampling from live animals because of the invasiveness of the sampling technique and the risk of hemorrhage; however, a study evaluating the safety of SP aspirations in dogs, concluded that this procedure was effective and safe for the diagnosis of L. infantum infection [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Serological assays are usually applied as screening tests because of their simple execution and rapid results, although, their accuracy for detecting canine visceral leishmaniosis (CanL) is limited [ 2 ]. Parasitological culture (PC) is considered the reference standard test, detecting L. infantum in 62.1 % to 82.2 % of seropositive dogs [ 3 , 4 ]. However, PC is time consuming and can be impaired by microbiological contamination [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation